Low Complexity Two-Dimensional Channel Estimation Algorithm for Broadband SC-FDE System - Qifeng Zou; Xuezhi Tan; Mei Liu; Yonggang Chi (Dianxin kexue)
Single carrier frequency domain equalization（SC-FDE）is widely recognized as an very promising technique for its lower peak-to-average power ratio, but it also needs more accurate channel estimation method. A low complexity two-dimensional MMSE channel estimation algorithm based on time-frequency domain separation feature of channel was proposed in order to improve estimation performance and predigest the complexity. The two-dimensional MMSE estimation can be simplified as two one-dimensional MMSE and the SVD algorithm was used to reduce the complexity of one-dimensional estimation. The UW as the cyclic prefix could reduce the overhead of system. Noise variance was also estimated at the UW. The simulation results show that the proposed algorithm has better performance than the conventional LS algorithm and MMSE algorithm. The complexity of the proposed algorithm was also lower than the conventional one-dimensional MMSE method.